Toxicity of Flame Retardant Isopropylated Triphenyl Phosphate: Liver, Adrenal, and Metabolic Effects. (July 2019) - Wade, Michael G.; Kawata, Alice; Rigden, Marc; Caldwell, Don; Holloway, Alison C.
The use of organophosphates phosphate flame retardants, particularly isopropylated triphenyl phosphate (IPTPP), has increased in recent years as replacements for polybrominated diphenyl ethers. This is despite limited understanding of the hazards of IPTPP. To examine the general and endocrine toxicity of IPTPP, adult Wistar rats were fed for 90 days on diets containing IPTPP estimated to deliver daily doses of 5 to 140 mg/kg/d. Exposure to IPTPP caused a dose-related increase in liver and adrenal gland weight in both sexes. Cells in the zona fasciculate (ZF) of the adrenal cortex were observed to be filled with droplets that stained with Nile red, suggesting they contained neutral lipid. Despite marked structural changes, there was no change in basal or stress-induced serum levels of their major secreted ZF product corticosterone (B), suggesting cell function was not altered. There were no effects on responses to glucose or insulin challenge, but serum levels of fructosamine were elevated by IPTPP exposure, suggesting a slight tendency of exposed animals to be hyperglycemic. Serum levels of total cholesterol and high-density lipoprotein cholesterol were significantly elevated in both sexes at the 2 highest doses. This study demonstrates that IPTPP exposure causes hypertrophy and neutral lipid accumulation in adrenal cortex ZF cells but does not result in impaired B production.